Pelatihan Peningkatan Kompetensi Mengajar dengan Menggunakan Bahasa Inggris Untuk Dosen-Dosen Program Studi S1 Manajemen, Universitas Kristen Satya Wacana - Ragawanti, Debora Tri; Antonina Anggraini Setiamunadi; Angga Widitama Putra; Jesicca Levina Shannon; Elisathusilawani , Elisathusilawani (LPPM UMRI, 2025)
The globalization era and the Industrial Revolution 5.0 demand not only technological proficiency but also fluency in English to enhance competitiveness in the workforce. Addressing this, the Management Study Program of the Faculty of Economics and Business, Universitas Kristen Satya Wacana (FEB UKSW), plans to expand English-medium instruction (EMI) classes. However, problems arise, including lecturers' lack of confidence and limited proficiency in teaching course content in English. A needs analysis involving eight lecturers revealed that while most have high TOEFL scores (75% above 500), 75% feel unprepared to teach in English due to limited mastery of classroom discourse strategies. To solve the problems, a training program was designed to enhance teaching competencies and confidence in using English. The program includes 14 sessions covering classroom management, questioning techniques, instructional strategies, and micro-teaching activities. Interactive methods, hands-on practice, and simulations were prioritized based on participants’ preferences. Results showed improved lecturer capabilities in delivering EMI, as well as increased confidence through structured practice and progressive learning. This initiative aligns with the need to equip lecturers with practical skills and confidence to teach content in English effectively, ensuring the program’s relevance and impact.